THE IDENTITY OF THE PAST AND PRESENT: CONTEXTS OF SOCIAL AND CULTURAL IDENTIFICATION OF THE SUBJECT - O. D. Garanina (Научный вестник МГТУ ГА, 2016)
The characteristic of national and cultural identity as necessary basis of unity of the subject and social community is given. Psychological, axiological and cognitive aspects of identity are allocated. The content of categories of social memory, social character and mentality as mechanisms of formation of social identity of the subject is defined. Social memory is considered as an embodiment of objective spirit (last historical experience of the mankind) forming the mental features of the subject acting as an identification matrix by means of social character. The dominating role of social memory in relation to social character and mentality in an identification context is proved.